PENGARUH KURIKULUM MULTIKULTURAL TERHADAP HABLU MINANNAS WA TASAMUH PESERTA DIDIK DI SMAN 1 KESAMBEN - Mubaidilla, Irfa'i Alfian; Mubaidilla, Trias Fatih; Fauzi, M (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2022)
This research aims to determine the effect of a multicultural-based education curriculum on social interactions and attitudes toward tolerance. Specifically, this research will analyze the effect of implementing a multicultural curriculum at SMAN 1 Kesamben on the social interactions and tolerance attitudes of students. The research approach uses a quantitative, correlational-type approach. The sampling technique used was a probability sample technique, a simple random sampling, and 71 respondents. The research results at the 5% significance level are as follows: There is a positive influence of the multicultural curriculum on social interaction, namely 29.3%. The constant value (constant) for social interaction is 20.439, and the coefficient value for the multicultural curriculum (X) is 0.910. In the sense that if there was no multicultural curriculum (X), the consistent value of social interaction (Y1) would be 20.439, and for every 1% additional contribution level of the multicultural curriculum (X), social interaction (Y1) would increase by 0.910. From this researcher, it was also obtained that the multicultural curriculum had a positive effect on attitudes toward tolerance. The influence of the multicultural curriculum (X) on tolerance attitudes (Y2) is 33.2%. The constant value for tolerance was 19.166, and the multicultural curriculum coefficient (X) value was 0.987. In the sense that if there is no multicultural curriculum (X), the consistent value of tolerance attitude (Y2) is 19.166, and for every 1% additional contribution level of the multicultural curriculum (X), tolerance attitude (Y1) will increase by 0.987.